Early Lexical and Grammatical Development of Xitsonga Spoken in Giyani, Limpopo Using the Adapted Xitsonga MacArthur-Bates Communicative Development Inventory: Toddlers Form A Preliminary Study - Ndhambi, Mikateko (Department of Health and Rehabilitation Sciences, 2025)
Background: Speech-language pathologists have limited culturally and linguistically relevant clinical assessments and normative data to draw on when working with African language speakers in South Africa. This limitation impacts on the early identification of children with language difficulties, essential for ensuring appropriate and timely support for such children and their families. The challenge of early identification is even more pronounced for children acquiring a minority language such as Xitsonga. Xitsonga is one of South Africa's official languages, yet relatively little is known about children's acquisition of this language. Aims and objectives: This study aimed to describe the early lexical and grammar development of Xitsonga-speaking children, aged 16 to 32 months. The study objectives were to describe 1) the outcomes of the adaptation of the MacArthur-Bates Communicative Development Inventory (MB-CDI) for Xitsonga speakers 2) the relationship between age and vocabulary size 3) the trends and patterns of vocabulary growth and grammar development and 4) the development of mean length of utterance in this population. Methods: The study used a mixed methods approach. For Phase one, a parentreport tool, the MB-CDI, was cross-culturally adapted for Xitsonga. Phase two was a pilot study where the first draft of the Xitsonga MB-CDI was administered to 43 caregivers of monolingual Xitsonga-speaking children aged 16 to 32 months in the Giyani region of South Africa's Limpopo Province. Descriptive statistics and Pearson's correlations were used to determine the lexical and grammatical items included in the main study. Phase three was the administration of the adapted Xitsonga MB-CDI with a larger sample (n=99) of caregivers of monolingual Xitsonga-speaking children aged 16 to 32 months residing in the Giyani region, who had not already participated in the pilot study. Vocabulary sizes, compositions, and morphosyntactic productions were outlined using descriptive statistics. Pearson's correlations and independent t-tests were done to describe correlations between age and the aforementioned variables. Results: The adaptation/translation of the MB-CDI, focus groups and pilot study ensured the Xitsonga CDI was culturally and linguistically acceptable and effective for documenting 16 to 32 months old children's lexical and grammatical abilities. The findings of the pilot study showed a strong correlation between age and the items frequently used by Xitsonga-speaking children in this study. This guided the inclusion and exclusion of items for the adapted Xitsonga MB-CDI used as a tool in the main study to describe the early lexical and grammar development of Xitsonga. Findings from the final phase of the study confirm the prediction of an increase in vocabulary production with an increase in age, as expected in typically developing children. This reflects a linear correlation (r = .45; p < .001) with age accounting for 20.5% of the variance. Of the total items in the Xitsonga MB-CDI, common nouns made up the largest proportion of acquired words (322 items), followed by predicates (208 items) and function words (68 items). As for other languages, age has a significant effect (F[1,97] = 33.2; r = .51; p < .001) on children's grammatical development, accounting for 25.91% of the variance. The mean sentence length-morpheme (MSL-m) yielded a higher score than the mean sentence length-word (MSL-w) in Xitsonga. Both showed a weaker correlation with vocabulary size (r = .11; p > .05 and r = .10; p > .05, respectively) but a stronger correlation with sentence complexity (r = .25; p < .05 and r = .20; p < .05, respectively). However, there was a linear relationship between vocabulary and grammar used by Xitsonga-speaking children in this sample. Vocabulary development showed a stronger correlation with sentence complexity (r = .45; p < .001) and also with total grammar development (r = .40; p < .001). Implications: From an applied perspective, the study contributes new and much-needed knowledge about children's early acquisition of Xitsonga vocabulary and grammar. This information is important for helping clinicians, families and early childhood development practitioners identify and support children with delayed language development and their families. The study provides a foundation of preliminary data about what is typical for children acquiring Xitsonga. It also supplies the initial version of a tool to assess young speakers of this language. From a theoretical standpoint, the findings enable cross-linguistic comparisons with the acquisition of other languages and contribute to a broader understanding of the universal aspects of language acquisition in young children. KEYWORDS: Xitsonga, early lexical development, early grammar development, cross-cultural adaptation, MacArthur-Bates Communicative Development Inventory (MB-CDI).